Fabrication of Ag-Ag2O/reduced TiO2 nanophotocatalyst and its enhanced visible light driven photocatalytic performance for degradation of diclofenac solution - Cui, Yuqi; Ma, Qiuling; Deng, Xiaoyong; Meng, Qi; Cheng, Xiuwen; Xie, Mingzheng; Li, Xiaoli; Cheng, Qingfeng; Liu, Huiling (Applied catalysis. B, Environmental, 2017)
[Display omitted] •Ag-Ag2O/r-TiO2 photocatalyst was fabricated through solution reduction strategy.•Ag-Ag2O/r-TiO2 exhibited higher photoinduced charge separation efficiency.•Contribution of each species to the degradation of diclofenac was distinguished.•The enhanced visible light driven (VLD) PC mechanism was confirmed in detail. In this study, Ag-Ag2O/reduced TiO2 (denoted as Ag-Ag2O/r-TiO2) nano-photocatalyst had been fabricated through one-step solution reduction strategy in the presence of potassium borohydride. Afterwards, physicochemical properties of the resulting samples were investigated by scanning electron microscope (SEM), N2 adsorption/desorption isotherms, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV–vis diffuse reflectance spectroscopy (UV-vis DRS), electron spin resonance (ESR) and time-resolved surface photovoltage (TR-SPV) techniques. Results indicated that potassium borohydride treatment could simutaneously induce the generation of Ti3+ self-doping energy level between the forbidden band of TiO2 and metallic Ag species existed in the forms of Ag0 and Ag2O nanocrystalline, thereby resulting in the greatly enhanced visible light absorbance and photoinduced charge separation efficiency. In addition, the visible light driven (VLD) photocatalytic (PC) performance was evaluated through the degradation of diclofenac and generation of ·OH radicals. As-expected, Ag-Ag2O/r-TiO2 sample exhibited higher VLD PC performance and larger generation amount of ·OH radicals. Furthermore, the enhanced VLD PC mechanism was proposed and confirmed, which was mainly attributed to the synergistic effect originated from the localized SPR of Ag0 nanocrystalline and Ti3+ self-doping which responsible for the intense visible light absorbance, high photoinduced charge separation efficiency and VLD PC performance.